Social sciences vital, too - Mohd Sani, Mohd Azizuddin (New Straits Times, 2011)
MALAYSIA, in the process of becoming a developed stated, must strengthen its research and development (R&D) activities, not only in sciences and technology but also in social scienes and humanities.